DEVELOPMENT OF THE URBAN HYDROLOGICAL DISASTERS SUSCEPTIBILITY INDEX - Rafael Brandao Ferreira de Moraes (2023)
The increase in the rate of urbanization linked to inadequate planning of cities and changes in land use and occupation are modifying the surface runoff and infiltration processes of rainwater in the urban areas of several municipalities, contributing to the occurrence of hydrological disasters (floods). At the same time, it is important to highlight the scarcity of consistent and reliable hydrological data on a satisfactory spatio-temporal scale for carrying out hydrological studies, especially in area that is difficult to access, extensive and with low financial resources. In this context, precipitation estimates via remote sensing emerge as promising alternatives to complement surface measurements. The general objective of this work was to develop, apply and validate the Urban Hydrological Disaster Susceptibility Index (UHDSI) from indicators pertinent to different spheres (morphometry, land use and occupation, rainwater infrastructure and environmental), taking into account both infiltration and surface runoff of rainwater in Campo Grande - Mato Grosso do Sul (MS) - Brazil, presented in the first chapter. The results of the UHDSI and historical records of floods applied in each Urban Hydrographic Micro-basins (UHM) obtained a strong correlation (r > 0.80), evidencing the reliability and validation of the developed index. In this way, the UHDSI is capable of assisting in the formulation of appropriate political measures and legal norms for ordering land use and occupation, as well as indicating the UHMs that need more attention and mitigating actions from the public power for sustainable socioeconomic development. From the scarcity of reliable and consistent precipitation data verified during the development of the UHDSI in the city of Campo Grande - MS, two new studies were carried out in order to statistically validate the Tropical Rainfall Measurement Mission (TRMM) precipitation estimates in the five geographic regions of the Brazil and to compare the performances of the Global Precipitation Measurement (GPM), TRMM and Global Precipitation Climatology Project (GPCP) precipitation estimates in the daily, monthly and seasonal time scales in the municipality of Campo Grande - MS presented in the second and third chapter, respectively. In general, the results showed that caution is needed before using precipitation estimates on the daily scale, since excellent statistical results were not found on this time scale. However, increasing the time scale considerably improves the correlation and agreement between the precipitation data estimated via remote sensing and the precipitation data observed on the surface, making it possible to better represent the rainfall pattern in the area of interest. Finally, it is expected that the results of this research will help in the planning of various socioeconomic activities that involve precipitation data, such as agriculture, livestock, power generation and identification of areas susceptible to hydrological disasters in regions with climates characterized by dry winters and humid summers.